2017
DOI: 10.1007/s00268-017-4079-3
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors for Postoperative Delirium in Patients After Hepatectomy

Abstract: This study clarified the incidence and risk factors for delirium after liver resection. These results would contribute to prediction and treatment of delirium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 28 publications
4
37
2
3
Order By: Relevance
“…It was reported that an advanced age, low serum albumin level and a high probability of preoperative cerebrovascular disorders were independent risk factors for post‐operative delirium in patients after liver resection, while these features were also observed in the current meta‐analysis (Table ). Perioperative intervention, including psychiatric consultation, albumin level tests and perioperative risk evaluation and monitoring, should be strongly considered for the prevention and early treatment of post‐operative delirium …”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…It was reported that an advanced age, low serum albumin level and a high probability of preoperative cerebrovascular disorders were independent risk factors for post‐operative delirium in patients after liver resection, while these features were also observed in the current meta‐analysis (Table ). Perioperative intervention, including psychiatric consultation, albumin level tests and perioperative risk evaluation and monitoring, should be strongly considered for the prevention and early treatment of post‐operative delirium …”
Section: Discussionsupporting
confidence: 55%
“…Post‐operative delirium occurred at a high rate of 33.1% among super‐elderly patients in the current meta‐analysis, which was also higher than the reported rates ranging from 8.4 to 22% among patients of a younger age, ranging from 65 to 71 years, after liver resection . It was reported that an advanced age, low serum albumin level and a high probability of preoperative cerebrovascular disorders were independent risk factors for post‐operative delirium in patients after liver resection, while these features were also observed in the current meta‐analysis (Table ). Perioperative intervention, including psychiatric consultation, albumin level tests and perioperative risk evaluation and monitoring, should be strongly considered for the prevention and early treatment of post‐operative delirium …”
Section: Discussionsupporting
confidence: 41%
“…In the past, many studies focused on the mortality and long-term survival of the patients after hepatectomy [25–27]. However, limited studies have been developed to determine which perioperative parameters were the risk factors influencing the postoperative complications of liver resection [1416, 28]. The Surgical Apgar Score (SAS), which was first proposed in 2007 by Gawande et al [29], is a 10-point model made up of three intraoperative parameters: mean arterial pressure (MAP), heart rate (HR), and estimated blood loss (EBL).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, more and more studies have been focused on the strategies not only to prevent the mortality but also to predict the nonlethal postoperative complications. Many studies have been proposed to identify risk factors of postoperative complications and then to help patients not at high risk of poor outcome after surgery [1416].…”
Section: Introductionmentioning
confidence: 99%
“…Another study found that a postoperative hemoglobin level of <11 g/dl, which is similar in nature to intraoperative blood loss of ≥1000 ml, was a risk factor for postoperative delirium [ 6 ]. Two previous studies have reported that a low serum albumin level is a risk factor for postoperative delirium [ 4 , 5 ]. However, no such finding was obtained in the present study.…”
Section: Discussionmentioning
confidence: 99%